"Performance comparison of innovative spiral shaped solar collector design with conventional flat plate solar collector". (1st March 2020) - Verma, Sujit Kumar; Sharma, Kamal; Gupta, Naveen Kumar; Soni, Pawan; Upadhyay, Neeraj
Abstract: Flat plate solar collector is an essential device, which facilitate direct application of solar energy for water heating in household and industrial sector. Existing Flat plate solar collectors (FPSC) suffers from stagnant and comparatively low efficiency. Further research to improve efficiency of FPSC by inculcating innovative design is necessary. To fill the gap, the presented work is an experimental investigation of an innovative design and fabrication approach which deals with analysis of flat plate solar collector efficiency. Design modifications of solar collector always offer an important alternative to achieve significant effect on thermal efficiency. In this work single spiral shaped collector tube as compare to number of riser tubes connected with headers in conventional type flat plate solar collector has been developed. Keeping all other parameters similar to conventional design, it has been observed very encouraging outcomes in efficiencies of solar collector. Under forced mode of testing, enhancement in thermal efficiency achieved is, 21.94% compared to conventional flat plate collector design. Enhancement in exergy efficiency is 6.73%. Overall material saving is about ∼30% and cost of manufacturing and maintenance can be significantly reduced at equivalent performance of conventional collector. Highlights: Progress of civilization is driven by energy. Material and maintenance cost can be further reduced. Entropy generation for spiral collector is moderately lesser. Thermal efficiency for spiral tube collector is higher. Exergy efficiency is reciprocal to growth in entropy.